2016
DOI: 10.1556/1846.2016.00015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles Using a Microfluidic Impinging Jet Reactor

Abstract: Synthesis of silver nanoparticles (NPs) in an impinging jet reactor (IJR) was investigated due to its unique properties of efficient mixing and lack of channel walls which avoid fouling. Silver NPs were formed at room temperature by reducing silver nitrate with sodium borohydride in the presence of sodium hydroxide. Two types of ligand were used to stabilize the NPs, trisodium citrate, and polyvinyl alcohol (PVA). Weber number, the ratio between inertial forces and surface tension forces, is used to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Recent advances in their synthesis include the use of microfluidic reactors for continuous growth of the particles. 79,94 AgNPs have bluer LSPR bands than AuNPs and stronger field enhancements. 95 Thus, since the publication of the early synthetic protocols, AgNPs were successfully used as a substrate for SERS.…”
Section: Different Classes Of Mnpsmentioning
confidence: 99%
“…Recent advances in their synthesis include the use of microfluidic reactors for continuous growth of the particles. 79,94 AgNPs have bluer LSPR bands than AuNPs and stronger field enhancements. 95 Thus, since the publication of the early synthetic protocols, AgNPs were successfully used as a substrate for SERS.…”
Section: Different Classes Of Mnpsmentioning
confidence: 99%
“…B z enabled higher We and better mixing by rotation and resulted in d av 2.5 nm at We 39.1. Baber et al reported using a clog-free microfluidic impinging jet microreactor to synthesize very small AgNPs and obtained AgNPs that was approximately d av 4.1 nm at We 65.0 (Baber et al, 2016). IMS enabled the synthesis of even smaller AgNPs, which indicated the significant potential of IMS.…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%
“…This technique can be applied for atomization of the high viscosity and non-Newtonian liquids such as the gelled fuels because of its simplicity and high-performance mixing and atomization [3]. In chemical reactors, impinging of two jets can be used in crystallization and precipitation process [4], [5], synthesis of silver nanoparticles [6], and forming clathrate hydrates [7]. Impinging jets also can be developed with the UV/H 2 O 2 reactors for wastewater treatment [8].…”
Section: Introductionmentioning
confidence: 99%